A constituição de sujeitos e sentidos em contextos de ensinoaprendizagem de língua inglesa e seus reflexos na profissionalização - Mudo, Relma Lúcia Passos de Castro (2009)
Because of the enlargement of commercial frontiers in the region of São Francisco valley, the crescent number of school idioms in Petrolina-PE city, the globalization and its repercussion in the socio-historical-cultural process and the appearance of exportation and importation companies of products and service in the region, the present dissertation has as objective to investigate the importance of English Language domain in Secretariado Executivo and Comércio Exterior courses at FACAPE in the work market in reference to communication process, spoken or written one. The theoretic guide is centered in Discourse Analysis presupposes, of French orientation, that reflects about the elements which moves the relations among discourse, culture, history, subject and sense, and also it recommends a theoretic board which align them to the English language and the learning, for indicating how the idiom has influenced in the professional inclusion and exclusion of the involved subjects. The discursive corpus is constituted by a set of discursive sequences, obtained in semi-structured interviews. To this, the students and professor s conceptions were investigated which refer to English Language teaching-learning and the professional practice in the courses mentioned above, and also the employment expectations in relation to the work market requirements of a VALEXPORT company s representative. Five students from Secretariado Executivo and Comércio Exterior Courses, three professors from FACAPE who teach English Language and two employees from VALEXPORT Company contributed to the research. The caught result proposes, to the students, contributions to a critical reflection of the mentioned problems. So, by understanding better the society dynamism where they live, could notice themselves as life elements of political force and transforming capacity, and also make structured changes which point to a fairer society.